What Are the Benefits of AI in Cognitive Behavioral Therapy? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Cognitive Behavioral Therapy (CBT) has long been a cornerstone of modern psychotherapy, providing an evidence-based approach to treating a wide array of ment...
Keywords: AI in Mental Health; Benefits; Cognitive; Behavioral; Artificial Intelligence; Healthcare